The efficacy of indoximod upon stimulation with pro-inflammatory cytokines in triple-negative breast cancer cells. (3rd September 2021) - Guney Eskiler, Gamze; Bilir, Cemil
Abstract: Background: Indoleamine 2, 3-dioxygenase (IDO) inhibition has received much attention in cancer immunotherapy due to its role in immune escape in cancer cells. Additionally, changes in the pro-inflammatory cytokine levels can affect tumor growth and metastasis as well as the effectiveness of immunotherapy. The purpose of this study was for the first time to determine the effects of indoximod as an IDO inhibitor on triple-negative breast cancer (TNBC) and to assess the link between the efficacy of indoximod and IFN-γ or TNF-α stimulation. Methods: The cytotoxic and apoptotic effects of indoximod alone or IFN-γ or TNF-α induction to mimic an inflammatory environment were evaluated by WST-1, Annexin V, cell cycle analysis, and acridine orange (AO)/ethidium bromide (EtBr) staining. Furthermore, the expression levels of IDO1 and PD-L1 expression were analyzed by RT-PCR. Results: Our results demonstrated that indoximod significantly decreased the TNBC cell viability through apoptotic cell death ( p < .05). The combination of indoximod and TNF-α was more effective than indoximod and IFN-γ stimulation or indoximod alone in TNBC cells. Additionally, PD-L1 expression level was significantly up-regulated after treatment with indoximod and TNF-α or IFN-γ combinations ( p < .05). Conclusions: Indoximod exhibited a therapeutic potential in TNBC cells and pro-inflammatory cytokines could affect the effectiveness of indoximod. However, further studies are required to identify the role of the IDO-associated signaling pathways, the molecular mechanisms of indoximod induced apoptotic cell death, and the relationship between IDO inhibition by IDO inhibitors and pro-inflammatory cytokine levels.